New Endocrine Syndrome: Insular and Carcinoid with Virilization - Praderi, Raúl; Bogliaccini, Gustavo; Gómez Haedo, Carlos; Temesio, Perla; Rodríguez, Laura; Bonifazio, Juan; Cassinelli, Mauricio (Cirugía del Uruguay, 1980)
Report on one case of complex endocrine syndrome in a 61 - year - old female patient who suffered from insuJ'ar syndrome and virilization.